2023
DOI: 10.1111/btp.13195
|View full text |Cite
|
Sign up to set email alerts
|

Climate and microhabitat shape the prevalence of endozoochory in the seed rain of tropical montane forests

Abstract: Endozoochory, the dispersal of seeds by animal ingestion, is the most dominant mode of seed dispersal in tropical forests and is a key process shaping current and future forest dynamics. However, it remains largely unknown how endozoochory is associated with environmental conditions at regional and local scales. Here, we investigated the effects of elevation, climate, and microhabitat conditions on the proportion of endozoochorous plant species in the seed rain of the tropical Andes of southern Ecuador. Over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…After fire or land abandonment, bracken fern, Pteridium spp., frequently colonizes deforested areas and dominates the vegetation for long periods, hindering forest regeneration (Carvalho et al., 2022; Hartig & Beck, 2003; Ssali et al., 2017). Since most tropical forest tree species are dispersed by animals (Acosta‐Rojas et al., 2023; Howe & Smallwood, 1982; Moles et al., 2007), forest regeneration in the deforested areas is highly dependent on seed‐dispersing animals (Catterall, 2018; Costa et al., 2022; Wunderle, 1997). Although the seed rain and seedling recruitment of forest tree species in bracken‐dominated areas is low (Gallegos et al., 2016; Saavedra et al., 2015; Ssali et al., 2018), the properties of seed disperser communities in tropical bracken‐dominated areas have not been studied (but see Maya‐Elizarrarás & Schondube, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After fire or land abandonment, bracken fern, Pteridium spp., frequently colonizes deforested areas and dominates the vegetation for long periods, hindering forest regeneration (Carvalho et al., 2022; Hartig & Beck, 2003; Ssali et al., 2017). Since most tropical forest tree species are dispersed by animals (Acosta‐Rojas et al., 2023; Howe & Smallwood, 1982; Moles et al., 2007), forest regeneration in the deforested areas is highly dependent on seed‐dispersing animals (Catterall, 2018; Costa et al., 2022; Wunderle, 1997). Although the seed rain and seedling recruitment of forest tree species in bracken‐dominated areas is low (Gallegos et al., 2016; Saavedra et al., 2015; Ssali et al., 2018), the properties of seed disperser communities in tropical bracken‐dominated areas have not been studied (but see Maya‐Elizarrarás & Schondube, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical elevational gradients are suitable for studying spatial variation in forest restoration dynamics (González et al, 2013;Silveira et al, 2019) because they cover a wide range of abiotic and biotic conditions over a small spatial extent (Bruijnzeel & Veneklaas, 1998;Sanders & Rahbek, 2012). Furthermore, previous studies have shown that the diversity of woody plant species and plant trait composition change along elevational gradients (Aide et al, 1996;Acosta-Rojas et al, 2023). The diversity of seed-dispersal interactions between plants and their animal seed dispersers also changes along tropical mountains (Quitián et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the classic definition, a fruit is a developed carpel that usually helps to protect and disseminate seeds (Gonçalves, 2021). Overall, a large diversity of fruit shapes and functions are present in plant communities (e.g., van Roosmalen, 1985; Acosta‐Rojas et al, 2021; Stevenson, 2023). Within one tropical site, fruits may be represented by dozens of different types, with enormous variation in morphological traits.…”
mentioning
confidence: 99%